2004
DOI: 10.1111/j.1471-4159.2004.02715.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐transplantation of carotid body and ventral mesencephalic cells as an alternative approach towards functional restoration in 6‐hydroxydopamine‐lesioned rats: implications for Parkinson's disease

Abstract: Exogenous administration of various neurotrophic factors has been shown to protect neurons in animal model of Parkinson's disease (PD). Several attempts are being made to search a tissue source simultaneously expressing many of these neurotrophic factors. Carotid body (CB) contains oxygen-sensitive glomus cells rich in dopamine (DA) and expresses glial cell line-derived neurotrophic factor, brain-derived neurotrophic factor and neurotrophin-3. We have attempted to study the functional restoration following co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 66 publications
(139 reference statements)
0
15
0
Order By: Relevance
“…Lesioned rats were divided into four groups and cells were transplanted in CA3 region of hippocampus at 4 weeks post‐lesioning following the coordinates AP 3.7 mm, L 4.1 mm, and V 4.5 mm. For co‐transplantation, cultured OECs and NPCs were mixed in equal number to make a homogenous suspension (Shukla et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Lesioned rats were divided into four groups and cells were transplanted in CA3 region of hippocampus at 4 weeks post‐lesioning following the coordinates AP 3.7 mm, L 4.1 mm, and V 4.5 mm. For co‐transplantation, cultured OECs and NPCs were mixed in equal number to make a homogenous suspension (Shukla et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Among these variables are the local changes of pressure, which could cause modifications unrelated with the neurotrophic effect of the protein, or the amount of GDNF being released, because it is known that excessive striatal GDNF expression produces downregulation of TH and aberrant axonal sprouting in downstream brain areas (Georgievska et al, 2002;Rosenblad et al, 2003). Intrastriatal grafting of CB tissue has been shown to produce notable dopaminergic reinnervation and behavioral recovery in parkinsonian rats (Espejo et al, 1998;Hao et al, 2002;Toledo-Aral et al, 2002Shukla et al, 2004) and monkeys (Luquin et al, 1999). In rodents, CB grafts are maintained stable, with metabolically active dopamine-and GDNF-producing glomus cells for the entire animal lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been postulated that macrophages activated after rupture of the brain-blood barrier in intracerebral grafts can produce neurotrophic factors and induce axonal sprouting (Batchelor et al, 1999). Although the lack of striatal reinnervation in the sham-operated parkinsonian animals (Espejo et al, 1998;Luquin et al, 1999;Hao et al, 2002;Shukla et al, 2004) have already demonstrated the specificity of CB graft effects, we wondered whether GDNF is upregulated in brain parenchyma or in macrophages after CB grafting and/or brain damage. To address this question, we performed CB (from 1-to 2-month-old wildtype donors) or sham transplants in host heterozygous GDNF/lacZ animals (2-3 months old).…”
Section: Gdnf Expression In Glomus Cells Of Intrastriatal Cb Graftsmentioning
confidence: 99%
“…Moreover, CB grafts performed in young rats remain active for the entire animal lifespan. 22 23 Transplantation of CB cell aggregates has been shown to induce Abbreviations: CAPIT, Core Assessment Programme for Intracerebral Transplantation; CAPSIT-PD, Core Assessment Programme for Surgical Interventional Therapies in Parkinson's Disease; CB, carotid body; GDNF, glial cell line derived neurotrophic factor; PD, Parkinson disease; PET, positron emission tomography; TH, tyrosine hydroxylase; UPDRS, Unified Parkinson's Disease Rating Scale a neurotrophic mediated recovery in animal models of PD [22][23][24][25][26][27] and stroke. 28 29 We conducted a phase I-II video blinded clinical study to assess the long term safety, clinical and neurochemical effects of intrastriatal CB autotransplantation in patients with advanced PD.…”
mentioning
confidence: 99%